Maternal Serum C-Reactive Protein in Women with Preterm Prelabor Rupture of Membranes - Stepan, Martin (PLoS One, 2016)
OBJECTIVE: This study evaluated maternal C-reactive protein (CRP) as a predictor of microbial invasion of the amniotic cavity (MIAC) and histological chorioamnionitis (HCA) in women with preterm prelabor rupture of the membranes (PPROM) before and after 32 weeks of gestation. METHODS: This study was a prospective observational cohort study of 386 women. Maternal serum CRP concentrations were evaluated, and amniotic fluid samples were obtained via transabdominal amniocentesis at the time of admission. Placentas underwent histopathological examination after delivery. MIAC was defined based on a positive PCR for Ureaplasma species, Mycoplasma hominis and Chlamydia trachomatis and/or positive 16S rRNA gene amplification. HCA was defined based on the Salafia classification. RESULTS: Maternal CRP was significantly higher in women with MIAC and HCA (median 9.0 mg/l) than in women with HCA alone (median 6.9 mg/l), MIAC alone (median 7.4 mg/l) and without MIAC or HCA (median 4.5 mg/l) (p<0.0001). CRP was a weak predictor of the occurrence of MIAC and HCA before and after 32 weeks of gestation. Only the 95(th) percentile of CRP and PPROM before 32 weeks exhibited a false-positive rate of 1%, a positive predictive value of 90% and a positive likelihood ratio of 13.2 to predict MIAC and HCA. However, the low sensitivity of 15% limits the clinical utility of this detection. CONCLUSION: CRP is a poor predictor of the occurrence of MIAC and HCA, even at early gestational ages.